The Global Paediatric Surgery Network: Early Measures of Interest in the Website - Butler, M.W.; Krishnaswami, S.; Minocha, A. (European Journal of Pediatric Surgery, 2012)
Purpose The Global Paediatric Surgery Network (GPSN) website was launched in May 2010, with the following goals: to serve as a clearing house for pediatric surgery volunteer work performed worldwide, to provide online resources for surgeons working in areas of limited medical resources, and to provide practical and educational information for surgeons who wish to volunteer. The purpose of this study was to assess use of the website over the first year since its launch (May 6, 2010–May 5, 2011).Methods The GPSN website was examined for number of pages, number of listings in Past Work, Present Work, and Help Needed categories, as well as number of Volunteers Available. The online tool Google Analytics was used to assess parameters that measure use of the website, such as number of visits, number of page views, number of visitors, time on the website, and geographic origin of visitors.Results The GPSN website consists of 30 pages. There are 9 listings in Past Work, 23 listings in Present Work, and 13 listings in Help Needed categories. 118 people have registered as willing to volunteer, and 96 have indicated that they are able to work in times of a natural disaster. There were 8437 visits to the website, with 28 916 page views by 5170 visitors from 145 countries, with an average number of page views of 3.43 and an average time on the website of 4:05 min. The most visited pages were the homepage, the meetings page, and the pediatric surgery organizations page. 4 websites of pediatric surgery organizations have links to the GPSN website.Conclusions Based on early website use, we conclude that there is an interest in the GPSN. We speculate that participation in the GPSN will continue to grow, but that there is a continued need to promote the website in the global pediatric surgery community.
Keywords: surgical volunteerism; international surgery; global surgery; humanitarian surgery